Avoiding the humanitarian trap: The ‘Nobelization’ of food aid - Lanika Sanders (Thomas A. Lyson Center for Civic Agriculture and Food Systems, 2021)
Despite the significant role that hunger relief has played in global emergency response efforts throughout much of the last century—notably showcased with the 2015 naming of ‘Zero Hunger’ as the second Sustainable Development Goal, and more recently when the World Food Program was awarded the 2020 Nobel Peace Prize—significant hunger and malnutrition remain. Concerningly, past crises have demonstrated the potential for hunger relief efforts, particularly the provisioning of food aid, to undermine the ability of Global South countries and communities to recovery fully from shocks. This commentary takes a critical look at the role of food aid during extended crises and presents several thoughts for how aid agencies and Global North governments can continue to work toward Zero Hunger while simultaneously supporting Global South economies and cultures.